Energy transfer provision based on RF-Radio Frequency as an established solution of learning process using laptops and wireless projector. (February 2019) - Suroso, S; Sopian, S; Ade, H S; Ahmad, T
Abstract: Electrical energy is very crucial in whole aspects of our life. No exception with education. Closely related to education, this paper reports the research result concerning with mean, how to overcome power outage in a classroom. Research idea comes up from a situation in which electrical disruption occurs and its purpose is to propose the appropriate solution, namely by creating an apparatus consist of a pair of transmitter and receiver working on the base of radio frequency. There are former articles discussed how to transfer electrical energy by magnetic coupling, but have no invent in radio frequency transmission. It's different to them, the constructed apparatus will transmit the electrical energy through atmosphere media. The concept of radio frequency transmission and electrical generation are background of the creation of the prototype. In order to properly work, the prototype was composed from some modules. The purpose is to make it easier in case of replacement if there are malfunctions. The module consists of transmitter, receiver, multiplier, inverter and converter respectively. Simulation was carried out to optimize performance of the device before real construction. As a conclusion that the device can work well based on the observed output voltage.